2021
DOI: 10.3390/ijms23010354
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Clinical Implications of Variant Repeats in Myotonic Dystrophy Type 1

Abstract: Myotonic dystrophy type 1 (DM1) is one of the most variable monogenic diseases at phenotypic, genetic, and epigenetic level. The disease is multi-systemic with the age at onset ranging from birth to late age. The underlying mutation is an unstable expansion of CTG repeats in the DMPK gene, varying in size from 50 to >1000 repeats. Generally, large expansions are associated with an earlier age at onset. Additionally, the most severe, congenital DM1 form is typically associated with local DNA methylation. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 77 publications
0
11
0
1
Order By: Relevance
“…In addition, the length of the expansion increases over time [ 14 ]. In recent years, interruptions at the 5′ and 3′ ends of the CTG expansion of pathological DMPK transcripts have been described in around 3–5% of DM1 patients [ 15 , 16 ]. These sequences are mainly composed of unstable CCG, CGG, CTC and CAG interruptions, and they have been associated as a mechanism that increases phenotypical variability, although further studies to characterize their impact are needed.…”
Section: Myotonic Dystrophy Type 1 (Dm1)mentioning
confidence: 99%
“…In addition, the length of the expansion increases over time [ 14 ]. In recent years, interruptions at the 5′ and 3′ ends of the CTG expansion of pathological DMPK transcripts have been described in around 3–5% of DM1 patients [ 15 , 16 ]. These sequences are mainly composed of unstable CCG, CGG, CTC and CAG interruptions, and they have been associated as a mechanism that increases phenotypical variability, although further studies to characterize their impact are needed.…”
Section: Myotonic Dystrophy Type 1 (Dm1)mentioning
confidence: 99%
“…Forth, the majority of DM1 patients inherit pure CTG repeat expansion. However, more than 8% of known DM1 patients carry interruptions that vary in type (CCG, CAG, CTC and CGG) and number between families and also among individuals of the same family 12 . Interruptions are frequently associated with intergenerational contractions and stabilization of the CTG repeat as well as milder DM1 symptoms and / or additional symptoms 11,[13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Altered pattern of methylation around repeat expansions has been described in DM1 patients with VRs, which could potentially affect local gene expression and influence repeat instability [ 30 , 31 ]. The emergence of interruptions may be caused by multiple processes including spontaneous DNA damage, DNA repair and DNA polymerase errors occurring in germ cells and somatic cells throughout embryogenesis and the lifetime of DM1 patients [ 13 , 32 , 33 ]. The location of these interruptions changed dramatically between generations and the repeats tended to contract [ 27 , 31 , 34 ].…”
Section: Genetics Of Myotonic Dystrophiesmentioning
confidence: 99%
“…Another study of DM1 subjects showed that in patients without variant repeats (VRs), blood DNA methylation at baseline correlated with cognitive function 9 years later, independent of the number of CTG repeats; and patients with VRs (12 out of the total number of 115) had different DNA methylation and cognitive profiles [ 84 ]. Genetic and phenotypic features of reported individuals with VRs in the DMPK (CTG)n array have been summarized in a recent review by Meola’s group [ 32 ]. Patients with VRs have a different DNA methylation profile with higher downstream hypermethylation; however, the role of VRs in DM1 phenotype needs to be investigated by further studies.…”
Section: Postulated Pathomechanismsmentioning
confidence: 99%